KEABSAHAN PENDIRIAN PERSEROAN TERBATAS OLEH PEMEGANG SAHAM MELALUI PERJANJIAN NOMINEE - Fahlafi, Ramadhan Kahfi; Saleh , Moh. (Gapenas Publisher, 2025)
This study aims to analyze the validity of establishing a limited liability company through a nominee agreement and the legal consequences that arise if the deed of establishment is declared null and void. According to Law Number 40 of 2007 concerning Limited Liability Companies, a limited liability company (PT) is a legal entity established based on an agreement, and therefore subject to the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code. On the other hand, Law Number 25 of 2007 concerning Investment explicitly prohibits the use of nominee agreements in share ownership and declares such agreements null and void. This study uses a normative legal research method with a legislative and conceptual approach. Legal materials are analyzed systematically to find the relationship between the private law regime and state administrative law in the context of establishing a PT that contains nominee elements. The results of the study indicate that the establishment of a PT based on a nominee agreement contains a defect in the element of lawful cause, so that it is materially null and void. However, if the company has obtained legal entity approval from the competent minister, then based on the principle of presumption of legality, the approval decision is still considered valid and effective as long as it has not been revoked through the competent legal mechanism. Thus, there is a separation between the nullity of the establishment agreement in civil law and the continued validity of the administrative legal entity status. The legal consequences of this condition include the lapse of rights and obligations arising from the memorandum of association, without immediately removing the company's position as a legal entity vis-à-vis third parties acting in good faith. A solution can be sought through the mechanism of amending the articles of association in a GMS or through dissolution and a court decision in order to achieve harmony between material and formal validity